Reliability of the Evidence to Guide Decision-Making in Acupuncture for Functional Dyspepsia - Huang, Jinke; Liu, Jiali; Liu, Zhihong; Ma, Jing; Ma, Jinxin; Lv, Mi; Wang, Fengyun; Tang, Xudong (Frontiers in Public Health, 2022)
BACKGROUND & AIMS: There has been a significant increase in the number of systematic reviews (SRs) /meta-analyses (MAs) investigating acupuncture for functional dyspepsia (FD). To systematically collate, appraise and synthesize the current evidence, we carried out an umbrella review of SRs/MAs. METHODS: SRs/MAs on acupuncture for FD were collected by searching major medical databases. The included studies were evaluated in terms of methodological quality, reporting quality and quality of evidence using criteria from the Assessment of Multiple Systematic Reviews 2 (AMSTAR-2) tool, Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, and the Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) system, respectively. RESULTS: Ten SRs/MAs were analyzed for this study. The methodological quality, reporting quality and quality of evidence of the included SRs/MAs were generally unsatisfactory. Lack of protocol registration, no list of excluded trials, or lack of a comprehensive search strategy were the main limitations of included SRs/MAs. No high-quality evidence was found to support the effects of acupuncture for FD, the qualitative data synthesis relied on low quality trials with small simple sizes was the main factor for evidence degradation. CONCLUSINONS: Acupuncture seems to have promising efficacy in the treatment of FD. It provides a new and prospective therapeutic method for FD. Although the quality of the included SRs/MAs was generally low and defects were frequent, this umbrella review highlights areas where improvement in methodology is required.